2021
DOI: 10.3390/ani11061599
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chitosan and Naringin on Enteric Methane Emissions in Crossbred Heifers Fed Tropical Grass

Abstract: In order to meet consumer needs, the livestock industry is increasingly seeking natural feed additives with the ability to improve the efficiency of nutrient utilization, alternatives to antibiotics, and mitigate methane emissions in ruminants. Chitosan (CHI) is a polysaccharide with antimicrobial capability against protozoa and Gram-positive and -negative bacteria, fungi, and yeasts while naringin (NA) is a flavonoid with antimicrobial and antioxidant properties. First, an in vitro gas production experiment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…The lack of agreement between in vivo and in vitro studies may be, in part, due to the fact that the in vitro experiments did not consider the complex process of ruminal fermentation, rumen pH, the pattern of volatile fatty acids, absorption of VFA, passage rate, rumen dilution, anatomical differences of the rumen, and alterations in microbiome structure [ 32 ]. The number of experiments to quantify methane emissions when CHI is added to a ration in vivo are limited, but results in the current trial are consistent with the lack of decreased CH 4 production reported by Henry et al [ 31 ] in beef cattle and Jiménez-Ocampo et al [ 78 ] in crossbred heifers.…”
Section: Discussionsupporting
confidence: 88%
“…The lack of agreement between in vivo and in vitro studies may be, in part, due to the fact that the in vitro experiments did not consider the complex process of ruminal fermentation, rumen pH, the pattern of volatile fatty acids, absorption of VFA, passage rate, rumen dilution, anatomical differences of the rumen, and alterations in microbiome structure [ 32 ]. The number of experiments to quantify methane emissions when CHI is added to a ration in vivo are limited, but results in the current trial are consistent with the lack of decreased CH 4 production reported by Henry et al [ 31 ] in beef cattle and Jiménez-Ocampo et al [ 78 ] in crossbred heifers.…”
Section: Discussionsupporting
confidence: 88%
“…The addition of chitosan (3 000 molecular weight at 16 mg/g DM dosage) to fermentation could alter the fermentation route, favouring propionate and amylolytic bacteria (Jimenez-Ocampo et al 2021).…”
Section: Review Czech Journal Of Animal Sciencementioning
confidence: 99%
“…More specifically, by using a reverse mechanism, chitosan decreased the fibre concentration of silages, while simultaneously having a beneficial effect on NFC concentration and DM decomposition (Del Valle et al 2018). Chitosan altered the rumen fermentation pattern and boosted propionate synthesis, while simultaneously lowering cellulolytic bacteria such as Fibrobacter, Butyrivibrio, and Ruminococcus, hemicellulolytic bacteria such as Eubacterium, and increasing amylolytic bacteria (Goiri et al 2010;Dias et al 2017;Harahap et al 2020;Jimenez-Ocampo et al 2021). Chitosan can alter the profile of volatile fatty acids (VFA) by increasing propionate concentration (C 3 ) and thereby reducing the production of CH 4 , decreasing rumen NH 3 concentration and gas production.…”
Section: Review Czech Journal Of Animal Sciencementioning
confidence: 99%
“…The synthesis of acetate and butyrate is followed by the release of metabolic hydrogen, which has a deleterious impact on microbial development and on feed digestibility while accumulating in rumen fluid [ 10 , 21 ]. Some food additives can be effective in the laboratory but not in reality [ 22 ]. The use of naringin and chitosan positively affected fermentation patterns, increasing propionic acid while reducing acetate and methane production by 12% and 31%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The use of naringin and chitosan positively affected fermentation patterns, increasing propionic acid while reducing acetate and methane production by 12% and 31%, respectively. Still, for the in vivo trial where chitosan and naringin were administered either separately or in a combination given directly into the rumen, both additives did not show a positive effect on rumen fermentation or enteric methane production [ 22 ]. Other authors have studied seaweed‘s impact on methane emissions.…”
Section: Introductionmentioning
confidence: 99%